Developing Puzzle-Based Magic Box Media For Descriptive Writing Skills Of 5th Grade Elementary School Students: Pengembangan Media Magic Box Berbasis Puzzle Pada Keterampilan Menulis Deskripsi Siswa Kelas 5 Sekolah Dasar - Sartika Defianty; Muhammad Akhir; Tarman A. Arif (Academia Open, 2026)
General Background: Literacy development in elementary education requires innovative instructional media that support students in developing language skills, particularly descriptive writing. Specific Background: In many elementary classrooms, descriptive writing instruction remains dominated by conventional teaching methods with limited use of engaging learning media, which results in low student motivation and difficulty in generating ideas and organizing descriptive texts. Knowledge Gap: Existing studies have utilized puzzle or magic box media separately, yet limited research integrates both approaches into a single manipulative learning medium designed to guide the stages of descriptive writing. Aims: This study aims to develop and examine the prototype, validity, practicality, and effectiveness of puzzle-based Magic Box media for improving descriptive writing skills of fifth-grade elementary school students at SD Inpres Bonto-Bonto, Indonesia. Results: Using a Research and Development approach with the Four-D model (Define, Design, Develop, Disseminate), the developed media achieved high validity scores from media experts (93% and 81%) and material experts (96% and 80%). Practicality results showed learning implementation of 97%, teacher responses of 100%, and student responses averaging 99%. Effectiveness results indicated improved descriptive writing performance with an average score of 87 in limited trials and 88.44 in extensive trials, with all students achieving learning completion. Novelty: The innovation lies in integrating layered puzzles and QR Codes within a single manipulative medium that guides students from observation and vocabulary selection to sentence and paragraph construction. Implications: The puzzle-based Magic Box provides an interactive, structured, and hybrid learning medium that supports descriptive writing development, student engagement, and integrated digital literacy in elementary education. Highlights• Integrates layered puzzle activities with QR-based digital resources in a single manipulative learning medium.• Demonstrates high feasibility with expert validation scores above eighty percent across design and material aspects.• Produces strong student performance outcomes with complete learning mastery in classroom trials. KeywordsPuzzle-Based Magic Box; Descriptive Writing Skills; Elementary School Students; Instructional Media Development; Four-D Model